2021
DOI: 10.3390/ijms22168934
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and Distinct Elements of Phagocytosis in Human and C. elegans

Abstract: Endocytosis provides the cellular nutrition and homeostasis of organisms, but pathogens often take advantage of this entry point to infect host cells. This is counteracted by phagocytosis that plays a key role in the protection against invading microbes both during the initial engulfment of pathogens and in the clearance of infected cells. Phagocytic cells balance two vital functions: preventing the accumulation of cell corpses to avoid pathological inflammation and autoimmunity, whilst maintaining host defenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 260 publications
(278 reference statements)
0
9
0
Order By: Relevance
“…In the mouse brain, several reports indicate the capacity of astroglia to perform phagocytosis of apoptotic cells and their debris (Damisah et al, 2020; Konishi et al, 2020; Konishi et al, 2022; Morizawa et al, 2017). Given that studies in the invertebrate C. elegans , which lack professional phagocytes like macrophages, served as a foundation for our knowledge of genes regulating the molecular process of dying cell clearance (Conradt et al, 2016; Lukácsi et al, 2021), it is not entirely surprising that vertebrate neuroglia display such capacity. It is suggested that vertebrates developed specialization for managing phagocytic load through the use of professional phagocytes such as macrophages/microglia, possibly to reduce load on neuroglia, to in turn allow more specialized and complex neuroglial functions in the vertebrate central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse brain, several reports indicate the capacity of astroglia to perform phagocytosis of apoptotic cells and their debris (Damisah et al, 2020; Konishi et al, 2020; Konishi et al, 2022; Morizawa et al, 2017). Given that studies in the invertebrate C. elegans , which lack professional phagocytes like macrophages, served as a foundation for our knowledge of genes regulating the molecular process of dying cell clearance (Conradt et al, 2016; Lukácsi et al, 2021), it is not entirely surprising that vertebrate neuroglia display such capacity. It is suggested that vertebrates developed specialization for managing phagocytic load through the use of professional phagocytes such as macrophages/microglia, possibly to reduce load on neuroglia, to in turn allow more specialized and complex neuroglial functions in the vertebrate central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Using a simple invertebrate like C. elegans to model a human disease enables the deconstruction of complex molecular pathways into their individual components, resulting in valuable insights into the pathogenesis of a complex disease phenotype. [ 8 ] Notable examples are the discovery of major factors involved in apoptosis, phagocytosis and necrosis, [ 9–13 ] the discovery of key genes implicated in cancer, [ 14,15 ] the study of genes involved in neurodegenerative disorders, [ 16,17 ] and the discovery of genes regulating longevity like insulin/insulin‐like growth factor 1 (IGF1) signaling. [ 18 ] The C. elegans nematode is also becoming a popular platform for a deeper understanding of the underlying mechanism of anti‐parasitic agents and various human drugs, [ 19,20 ] as well as for discovering new bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The basic steps of phagocytosis are conserved across species [18][19][20] . In Drosophila, Draper is a major phagocytic receptor with roles in phagocytosis of bacteria, debris and apoptotic cells throughout the body.…”
Section: Introductionmentioning
confidence: 99%